Grobian Trouble: Grobianism and "Invectivity" in Thomas Murner and Martin Luther - Stauffer, Isabelle (Journal of Early Modern Christianity, 2023)
Thomas Murner's verse satire Von dem grossen Lutherischen Narren (1522) and Martin Luther's pamphlet Wider das Papsttum zu Rom, vom Teufel gestiftet (1545) are known as particularly grobian texts. This paper examines the grobian as a historically new key figure in these two pamphlets and views it in relation to the concept of "invectivity." Both are performative, violent, and in need of an audience. Moreover, their shared epistemic function is to question the existing order. The grobian also shows the contagiousness of "invectivity": both Murner and Luther profess grobianism - which they say they were forced into because their opponents adopted it. These attributions of grobianism raise the debate to the level of the metainvective. As a transmedial figure, the grobian helps to make debates about religious conflicts more figurative and visual. As a ridiculous figure, he challenges not only pejorative ridicule but also liberating laughter, and ex negativo demonstrates the utopia of polite behavior - thus going beyond "invectivity."